A genome-wide association study for diabetic nephropathy genes in African Americans - McDonough, Caitrin W.; Palmer, Nicholette D.; Hicks, Pamela J.; Roh, Bong H.; An, S Sandy; Cooke, Jessica N.; Hester, Jessica M.; Wing, Maria R.; Bostrom, Meredith A.; Rudock, Megan E.; Lewis, Joshua P.; Talbert, Matthew E.; et al. (Kidney international, 2011)
A genome-wide association study was performed using the Affymetrix 6.0 chip to identify genes associated with diabetic nephropathy in African Americans. Association analysis was performed adjusting for admixture in 965 type 2 diabetic African American patients with end-stage renal disease (ESRD) and in 1029 African Americans without type 2 diabetes or kidney disease as controls. The top 724 single nucleotide polymorphisms (SNPs) with evidence of association to diabetic nephropathy were then genotyped in a replication sample of an additional 709 type 2 diabetes-ESRD patients and 690 controls. SNPs with evidence of association in both the original and replication studies were tested in additional African American cohorts consisting of 1246 patients with type 2 diabetes without kidney disease and 1216 with non-diabetic ESRD to differentiate candidate loci for type 2 diabetes-ESRD, type 2 diabetes, and/or all-cause ESRD. Twenty-five SNPs were significantly associated with type 2 diabetes-ESRD in the genome-wide association and initial replication. Although genome-wide significance with type 2 diabetes was not found for any of these 25 SNPs, several genes, including RPS12, LIMK2, and SFI1 are strong candidates for diabetic nephropathy. A combined analysis of all 2890 patients with ESRD showed significant association SNPs in LIMK2 and SFI1 suggesting that they also contribute to all-cause ESRD. Thus, our results suggest that multiple loci underlie susceptibility to kidney disease in African Americans with type 2 diabetes and some may also contribute to all-cause ESRD.